Polycomb eviction as a new distant enhancer function. - Vernimmen, D; Lynch, MD; De Gobbi, M; Garrick, D; Sharpe, J; Sloane-Stanley, J; Smith, A; Higgs, D (2011)
Remote distal enhancers may be located tens or thousands of kilobases away from their promoters. How they control gene expression is still poorly understood. Here, we analyze the influence of a remote enhancer on the balance between repression (Polycomb-PcG) and activation (Trithorax-TrxG) of a developmentally regulated gene associated with a CpG island. We reveal its essential, nonredundant role in clearing the PcG complex and H3K27me3 from the CpG island. In the absence of the enhancer, the H3K27me3 demethylase (JMJD3) is not recruited to the CpG island. We propose a new role of long-range regulatory elements in removing repressive PcG complexes.